Effect of meal time on postprandial glycemia in patients with type 2 diabetes mellitus and obesity not receiving insulin - I. V. Misnikova; D. E. Zoloeva; A. A. Glazkov (Сахарный диабет)
BACKGROUND: Postprandial hyperglycemia (PPG) is associated with micro- and macrovascular diseases in patients with T2DM. Severity of postprandial peaks depends on composition and amount of food. Circadian rhythms can influence PPG, which may determine variability of glycemia during day. According to literature, in persons without T2DM, PPG is maximum after dinner. Features of the postprandial response in patients with T2DM are not effective enough.AIM: To assess variability of postprandial glycemia based on flash glucose monitoring (FGM) depending on meal times in patients with T2DM not receiving insulin.MATERIALS AND METHODS: Open prospective study. T2DM patients were managed on FMG FreeStyle Libre. Each patient carried out 9 tests with three types of food loads: boiled buckwheat (250 grams), apple (200 grams) and white bread (30 grams) for breakfast, lunch and dinner.Statistical analysis of PPG by area under glycemic curve (AUC) and area under glycemic curve excluding starting glycemia (delta AUC), analysis of glycemia before meals (Start_gly) was carried out. Effect of time of food intake and food type was assessed with a two-way RM ANOVA using R 4.1.2. for quantitative variables, arithmetic means and standard deviations (M±SD) are presented.RESULTS: A total of 29 patients were included. Data from 17 patients, 153 food loading tests, were included in analysis. Both food type (p=0.037) and time of food intake (p=0.003) were shown to have a significant effect on the AUC. Maximum AUC values were observed after breakfast (p=0.005 vs supper, p<0.001 vs dinner), and buckwheat intake (p=0.01 vs apple).For the delta AUC only type of food (p=0.003) had significant influence. Delta AUC was higher for buckwheat than for apple (p=0.001) and wheat bread (p=0.012).CONCLUSION: Patients with T2DM who do not receive insulin have higher PCG levels after breakfast compared to lunch and dinner, regardless of the type of food load. Rise in glucose after a food load relative to initial values does not significantly differ from time of a meal, which does not coincide with known data on the maximum rise in glycemia on a food stimulus after dinner, which is observed in individuals without DM2.